Anti-staphylococcal effect of enterocin in Sunar and yogurt - Lauková, A; Czikková, S; Burdová, O (Folia microbiologica, 1999)
Enterocin was used to control the growth of Staphylococcus aureus strains SA1 and Oxford 209P in Sunar (milk nourishment for suckling babies) and during the yogurt-making process. Reduction by three orders of magnitude was noted in the growth of SA1 strain in Sunar milk nourishment between the enterocin-containing (ES) and the control samples (CS) at 1-d cultivation. An inhibitory effect of enterocin was observed when surviving of SA1 cells were checked 6 h after the start of cultivation (2 h after enterocin application; enterocin was applied after 4 h). Decrease in the count of Oxford 209P strain in yogurt was detected in ES after 1 d of storage in comparison with CS (10(3) and 10(0) CFU mL-1 g-1). Thus a decrease by three orders of magnitude was found between ES and CS at the time mentioned. On the other hand, no bacteriocin activity was detected in ES after 1 d. Activity was detected only immediately after enterocin addition to ES (400 AU/mL) as well as after 1 and 3 1/2 h (200 AU/mL). Although the slight regrowth of the indicator was obtained up to 1 week of yogurt storage, the difference between ES and CS persisted. The lowest pH of the final yogurt product was noted in the reference yogurt sample but differences among the pH values of yogurt samples were not significant.
Keywords: potrava pro kojence; Humans; Milk; zvířata; mléko; kojenec; Animals; potravinářské konzervační látky; Food Preservatives; Infant Food; Staphylococcus aureus; Hydrogen-Ion Concentration; přemostěné cyklické sloučeniny; Bridged-Ring Compounds; koncentrace vodíkových iontů; jogurt; lidé; Infant; Yogurt